Discovery of New Genes Involved in Curli Production by a Uropathogenic Escherichia coli Strain from the Highly Virulent O45:K1:H7 Lineage - Nhu, Nguyen Thi Khanh; Phan, Minh-Duy; Peters, Kate M.; Lo, Alvin W.; Forde, Brian M.; Chong, Teik Min; Yin, Wai Fong; Chan, Kok Gan; Chromek, Milan; Brauner, Annelie; Chapman, Matthew R.; Beatson, Scott A.; et al. (American Society for Microbiology, 2018)
Curli are bacterial surface-associated amyloid fibers that bind to the dye Congo red (CR) and facilitate uropathogenic Escherichia coli (UPEC) biofilm formation and protection against host innate defenses. Here we sequenced the genome of the curli-producing UPEC pyelonephritis strain MS7163 and showed it belongs to the highly virulent O45:K1:H7 neonatal meningitis-associated clone. MS7163 produced curli at human physiological temperature, and this correlated with biofilm growth, resistance of sessile cells to the human cationic peptide cathelicidin, and enhanced colonization of the mouse bladder. We devised a forward genetic screen using CR staining as a proxy for curli production and identified 41 genes that were required for optimal CR binding, of which 19 genes were essential for curli synthesis. Ten of these genes were novel or poorly characterized with respect to curli synthesis and included genes involved in purine de novo biosynthesis, a regulator that controls the Rcs phosphorelay system, and a novel repressor of curli production (referred to as rcpA). The involvement of these genes in curli production was confirmed by the construction of defined mutants and their complementation. The mutants did not express the curli major subunit CsgA and failed to produce curli based on CR binding. Mutation of purF (the first gene in the purine biosynthesis pathway) and rcpA also led to attenuated colonization of the mouse bladder. Overall, this work has provided new insight into the regulation of curli and the role of these amyloid fibers in UPEC biofilm formation and pathogenesis. IMPORTANCE Uropathogenic Escherichia coli (UPEC) strains are the most common cause of urinary tract infection, a disease increasingly associated with escalating antibiotic resistance. UPEC strains possess multiple surface-associated factors that enable their colonization of the urinary tract, including fimbriae, curli, and autotrans-porters. Curli are extracellular amyloid fibers that enhance UPEC virulence and promote biofilm formation. Here we examined the function and regulation of curli in a UPEC pyelonephritis strain belonging to the highly virulent O45:K1:H7 neonatal meningitis-associated clone. Curli expression at human physiological temperature led to increased biofilm formation, resistance of sessile cells to the human cationic peptide LL-37, and enhanced bladder colonization. Using a comprehensive genetic screen, we identified multiple genes involved in curli production, including several that were novel or poorly characterized with respect to curli synthesis. In total, this study demonstrates an important role for curli as a UPEC virulence factor that promotes biofilm formation, resistance, and pathogenesis.